INTERPRETASI LINGKUNGAN PENGENDAPAN SUMUR R-2 BERDASARKAN ANALISIS ELEKTROFASIES - Hamriani Ryka; Jamaluddin Jamaluddin; Rianto Pasha; Fathony Akbar Pratikno (Sekolah Tinggi Teknologi MIGAS, 2020)
Characterization of the depositional environment is carried out by means of facies modeling analysis based on electrofacies which can provide rapid information about the depositional system of a rock formation. The purpose of this research is to interpret the determination of the depositional environment in the research area for the further development of exploration / exploitation of hydrocarbons. Methodology applied is gamma ray log interpretation (log GR) using the relative correlation between log shape variations and sedimentation facies. The approach in this study uses the interpretation of the log response pattern results including Serrated, Blocky, and Bell. Based on log interpretation, study area was deposited on transitional lower delta plain zone.